2019
DOI: 10.3390/s19081923
|View full text |Cite
|
Sign up to set email alerts
|

Characterized Bioelectric Signals by Means of Neural Networks and Wavelets to Remotely Control a Human-Machine Interface

Abstract: Everyday, people interact with different types of human machine interfaces, and the use of them is increasing, thus, it is necessary to design interfaces which are capable of responding in an intelligent, natural, inexpensive, and accessible way, regardless of social, cultural, economic, or physical features of a user. In this sense, it has been sought out the development of small interfaces to avoid any type of user annoyance. In this paper, bioelectric signals have been analyzed and characterized in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Bu et al 13 tested Time Delayed Feature (TDF) against Time-domain Features (TF) for continuous estimation of upper limb angles using the Random Forest (RF) algorithm. Tinoco et al 16 controlled a simple remote device with a 52 km distance through the internet using EMG as a proof of concept of an Internet of Things (IoT) application. Also, this paper presents EMG as an HMI that anyone with minimal education can use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu et al 13 tested Time Delayed Feature (TDF) against Time-domain Features (TF) for continuous estimation of upper limb angles using the Random Forest (RF) algorithm. Tinoco et al 16 controlled a simple remote device with a 52 km distance through the internet using EMG as a proof of concept of an Internet of Things (IoT) application. Also, this paper presents EMG as an HMI that anyone with minimal education can use.…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative method is to design controllers. 8,9 However for both condition diagnosis 10,11 and motion intention detection [12][13][14][15][16] it is shown that ML methods result in effective models that overcome the difficulties of EMG.…”
Section: Introductionmentioning
confidence: 99%